Endoscopic Endonasal Transmaxillary Transsphenoidal Approach for Excision of a Superior Orbital Fissure-Cavernous Sinus Meningioma: 2-Dimensional Operative Video. Issue 5 (28th April 2018) - El Refaee, Ehab; Fleck, Steffen; Matthes, Marc; Schroeder, Henry W S
Abstract: We present a 43-old-male who suffered from a slowly progressive loss of vision in the left eye. Magnetic resonance (MR) imaging revealed a well-circumscribed contrast-enhancing lesion in the region of the anterior cavernous sinus and superior orbital fissure that extended into the optic canal. A schwannoma or meningioma was suspected. A transcranial surgery performed at another institution was not successful in removing the tumor and further deterioration of vision occurred. After resection of the left middle turbinate, the sphenoid and maxillary sinus were opened. The bulging of the tumor was seen at the lateral wall of the sphenoid sinus. After bony decompression of the optic canal, the dura was opened. A meningioma was exposed that arose in between the dural layers of the cavernous sinus. A nice dissection plane was found and the tumor was circumferentially dissected and finally totally removed. There were no complications such as double vision or visual field deficit. MR imaging confirmed a total tumor resection. The visual acuity normalized within a few days. MR imaging obtained 3 yr after surgery shows no recurrence.